Combination of sago and soy-protein supplementation during endurance cycling exercise and subsequent high-intensity endurance capacity - Ghosh, A.K.; Rahaman, A.A.; Singh, R. (Human Kinetics Publ Inc, 2010)
The purpose of the study was to investigate whether a combination of sago and soy protein ingested during moderate-intensity cycling exercise can improve subsequent high-intensity endurance capacity compared with a carbohydrate in the form of sago and with a placebo. The participants were 8 male recreational cyclists with age, weight, and VO(2max) of 21.5 +/- 1.1 yr. 63.3 +/- 2.4 kg, and 39.9 +/- 1.1 ml . kg(-1) . min(-1), respectively. The design of the study was a randomized, double-blind placebo-controlled crossover comprising 60 min of exercise on a cycle ergometer at 60% VO(2max) followed by a time-to-exhaustion ride at 90% VO(2max). The sago feeding provided 60 g of carbohydrate, and the sago-soy combination provided 52.5 g of carbohydrate and 15 g of protein, both at 20-min intervals during exercise. Times to exhaustion for the placebo, sago, and sago-soy supplementations were 4.09 +/- 1.28, 5.49 +/- 1.20, and 7.53 +/- 2.02 min, respectively. Sago-soy supplementation increased endurance by 84% (44-140%; p < .001) and by 37% (15-63%; p < .05) relative to placebo and sago, respectively. The plasma insulin response was elevated above that with placebo during sago and sago-soy supplementations. The authors conclude that a combination of sago and soy protein can delay fatigue during high-intensity cycling.